Pathoblockers or antivirulence drugs as a new option for the treatment of bacterial infections - Calvert, Matthew B.; Jumde, Varsha R.; Titz, Alexander (Beilstein Journal of Organic Chemistry, 2018)
The rapid development of antimicrobial resistance is threatening mankind to such an extent that the World Health Organization expects more deaths from infections than from cancer in 2050 if current trends continue. To avoid this scenario, new classes of anti-infectives must urgently be developed. Antibiotics with new modes of action are needed, but other concepts are also currently being pursued. Targeting bacterial virulence as a means of blocking pathogenicity is a promising new strategy for disarming pathogens. Furthermore, it is believed that this new approach is less susceptible towards resistance development. In this review, recent examples of anti-infective compounds acting on several types of bacterial targets, e.g., adhesins, toxins and bacterial communication, are described.
Keywords: antimicrobial resistance; bacterial adhesins; bacterial toxins; pathoblockers; quorum sensing

Antimicrobial resistance surveillance in Europe 2015. Annual Report of the European Antimicrobial Resistance Surveillance Network (EARS-Net) - European Centre for Disease Prevention and Control (ECDC, 2017)

(untitled) - Cooper, M. A.; Shlaes, D. (Nature, 2011)

(untitled) - Rice, L. B. (J. Infect. Dis., 2008)

(untitled) - Chen, L.; Todd, R.; Kiehlbauch, J.; Walters, M.; Kallen, A. (Morb. Mortal. Wkly. Rep., 2017)

(untitled) - Dickey, S. W.; Cheung, G. Y. C.; Otto, M. (Nat. Rev. Drug Discovery, 2017)

(untitled) - Clatworthy, A. E.; Pierson, E.; Hung, D. T. (Nat. Chem. Biol., 2007)

(untitled) - Cegelski, L.; Marshall, G. R.; Eldridge, G. R.; Hultgren, S. J. (Nat. Rev. Microbiol., 2008)

(untitled) - Allen, R. C.; Popat, R.; Diggle, S. P.; Brown, S. P. (Nat. Rev. Microbiol., 2014)

(untitled) - Ernst, B.; Magnani, J. L. (Nat. Rev. Drug Discovery, 2009)

(untitled) - Sharon, N. (Biochim. Biophys. Acta, 2006)

(untitled) - Mydock-McGrane, L. K.; Hannan, T. J.; Janetka, J. W. (Expert Opin. Drug Discovery, 2017)

(untitled) - Choudhury, D.; Thompson, A.; Stojanoff, V.; Langermann, S.; Pinkner, J.; Hultgren, S. J.; Knight, S. D. (Science, 1999)

(untitled) - Bouckaert, J.; Berglund, J.; Schembri, M.; De Genst, E.; Cools, L.; Wuhrer, M.; Hung, C.-S.; Pinkner, J.; Slättegård, R.; Zavialov, A.; Choudhury, D.; Langermann, S.; et al. (Mol. Microbiol., 2005)

(untitled) - Fiege, B.; Rabbani, S.; Preston, R. C.; Jakob, R. P.; Zihlmann, P.; Schwardt, O.; Jiang, X.; Maier, T.; Ernst, B. (ChemBioChem, 2015)

(untitled) - Sperling, O.; Fuchs, A.; Lindhorst, T. K. (Org. Biomol. Chem., 2006)

(untitled) - Cusumano, C. K.; Pinkner, J. S.; Han, Z.; Greene, S. E.; Ford, B. A.; Crowley, J. R.; Henderson, J. P.; Janetka, J. W.; Hultgren, S. J. (Sci. Transl. Med., 2011)

(untitled) - Klein, T.; Abgottspon, D.; Wittwer, M.; Rabbani, S.; Herold, J.; Jiang, X.; Kleeb, S.; Lüthi, C.; Scharenberg, M.; Bezençon, J.; Gubler, E.; Pang, L.; et al. (J. Med. Chem., 2010)

(untitled) - Kleeb, S.; Jiang, X.; Frei, P.; Sigl, A.; Bezençon, J.; Bamberger, K.; Schwardt, O.; Ernst, B. (J. Med. Chem., 2016)

(untitled) - Mydock-McGrane, L.; Cusumano, Z.; Han, Z.; Binkley, J.; Kostakioti, M.; Hannan, T.; Pinkner, J. S.; Klein, R.; Kalas, V.; Crowley, J.; Rath, N. P.; Hultgren, S. J.; et al. (J. Med. Chem., 2016)

(untitled) - Bernardi, A.; Jiménez-Barbero, J.; Casnati, A.; De Castro, C.; Darbre, T.; Fieschi, F.; Finne, J.; Funken, H.; Jaeger, K.-E.; Lahmann, M.; Lindhorst, T. K.; Marradi, M.; et al. (Chem. Soc. Rev., 2013)

(untitled) - Cecioni, S.; Imberty, A.; Vidal, S. (Chem. Rev., 2015)

(untitled) - Hartmann, M.; Lindhorst, T. K. (Eur. J. Org. Chem., 2011)

(untitled) - Dubber, M.; Sperling, O.; Lindhorst, T. K. (Org. Biomol. Chem., 2006)

(untitled) - Lindhorst, T. K.; Dubber, M. (Carbohydr. Res., 2015)

(untitled) - Mayer, K.; Eris, D.; Schwardt, O.; Sager, C. P.; Rabbani, S.; Kleeb, S.; Ernst, B. (J. Med. Chem., 2017)

(untitled) - Schwartz, D. J.; Kalas, V.; Pinkner, J. S.; Chen, S. L.; Spaulding, C. N.; Dodson, K. W.; Hultgren, S. J. (Proc. Natl. Acad. Sci. U. S. A., 2013)

(untitled) - Kalas, V.; Hibbing, M. E.; Maddirala, A. R.; Chugani, R.; Pinkner, J. S.; Mydock-McGrane, L. K.; Conover, M. S.; Janetka, J. W.; Hultgren, S. J. (Proc. Natl. Acad. Sci. U. S. A., 2018)

(untitled) - Wagner, S.; Sommer, R.; Hinsberger, S.; Lu, C.; Hartmann, R. W.; Empting, M.; Titz, A. (J. Med. Chem., 2016)

(untitled) - Diggle, S. P.; Stacey, R. E.; Dodd, C.; Cámara, M.; Williams, P.; Winzer, K. (Environ. Microbiol., 2006)

(untitled) - Tielker, D.; Hacker, S.; Loris, R.; Strathmann, M.; Wingender, J.; Wilhelm, S.; Rosenau, F.; Jaeger, K.-E. (Microbiology (London, U. K.), 2005)

(untitled) - Chemani, C.; Imberty, A.; de Bentzmann, S.; Pierre, M.; Wimmerová, M.; Guery, B. P.; Faure, K. (Infect. Immun., 2009)

(untitled) - Sommer, R.; Joachim, I.; Wagner, S.; Titz, A. (Chimia, 2013)

Topics in Medicinal Chemistry - Titz, A. (Carbohydrate-Based Anti-Virulence Compounds against Chronic Pseudomonas aeruginosa Infections with a Focus on Small Molecules, 2014)

(untitled) - Joachim, I.; Rikker, S.; Hauck, D.; Ponader, D.; Boden, S.; Sommer, R.; Hartmann, L.; Titz, A. (Org. Biomol. Chem., 2016)

(untitled) - Casoni, F.; Dupin, L.; Vergoten, G.; Meyer, A.; Ligeour, C.; Géhin, T.; Vidal, O.; Souteyrand, E.; Vasseur, J.-J.; Chevolot, Y.; Morvan, F. (Org. Biomol. Chem., 2014)

(untitled) - Kadam, R. U.; Garg, D.; Schwartz, J.; Visini, R.; Sattler, M.; Stocker, A.; Darbre, T.; Reymond, J.-L. (ACS Chem. Biol., 2013)

(untitled) - Rodrigue, J.; Ganne, G.; Blanchard, B.; Saucier, C.; Giguère, D.; Shiao, T. C.; Varrot, A.; Imberty, A.; Roy, R. (Org. Biomol. Chem., 2013)

(untitled) - Wagner, S.; Hauck, D.; Hoffmann, M.; Sommer, R.; Joachim, I.; Müller, R.; Imberty, A.; Varrot, A.; Titz, A. (Angew. Chem., Int. Ed., 2017)

(untitled) - Pertici, F.; de Mol, N. J.; Kemmink, J.; Pieters, R. J. (Chem. – Eur. J., 2013)

(untitled) - Sommer, R.; Wagner, S.; Varrot, A.; Nycholat, C. M.; Khaledi, A.; Haussler, S.; Paulson, J. C.; Imberty, A.; Titz, A. (Chem. Sci., 2016)

(untitled) - Boukerb, A. M.; Decor, A.; Ribun, S.; Tabaroni, R.; Rousset, A.; Commin, L.; Buff, S.; Doléans-Jordheim, A.; Vidal, S.; Varrot, A.; Imberty, A.; Cournoyer, B. (Front. Microbiol., 2016)

(untitled) - Michaud, G.; Visini, R.; Bergmann, M.; Salerno, G.; Bosco, R.; Gillon, E.; Richichi, B.; Nativi, C.; Imberty, A.; Stocker, A.; Darbre, T.; Reymond, J.-L. (Chem. Sci., 2016)

(untitled) - Johansson, E. M. V.; Crusz, S. A.; Kolomiets, E.; Buts, L.; Kadam, R. U.; Cacciarini, M.; Bartels, K.-M.; Diggle, S. P.; Cámara, M.; Williams, P.; Loris, R.; Nativi, C.; et al. (Chem. Biol., 2008)

(untitled) - Boukerb, A. M.; Rousset, A.; Galanos, N.; Méar, J.-B.; Thepaut, M.; Grandjean, T.; Gillon, E.; Cecioni, S.; Abderrahmen, C.; Faure, K.; Redelberger, D.; Kipnis, E.; et al. (J. Med. Chem., 2014)

(untitled) - Hauck, D.; Joachim, I.; Frommeyer, B.; Varrot, A.; Philipp, B.; Möller, H. M.; Imberty, A.; Exner, T. E.; Titz, A. (ACS Chem. Biol., 2013)

(untitled) - Sommer, R.; Hauck, D.; Varrot, A.; Wagner, S.; Audfray, A.; Prestel, A.; Möller, H. M.; Imberty, A.; Titz, A. (ChemistryOpen, 2015)

(untitled) - Sommer, R.; Exner, T. E.; Titz, A. (PLoS One, 2014)

(untitled) - Sommer, R.; Wagner, S.; Rox, K.; Varrot, A.; Hauck, D.; Wamhoff, E.-C.; Schreiber, J.; Ryckmans, T.; Brunner, T.; Rademacher, C.; Hartmann, R. W.; Brönstrup, M.; et al. (J. Am. Chem. Soc., 2018)

(untitled) - Garland, M.; Loscher, S.; Bogyo, M. (Chem. Rev., 2017)

(untitled) - Wilcox, M. H.; Gerding, D. N.; Poxton, I. R.; Kelly, C.; Nathan, R.; Birch, T.; Cornely, O. A.; Rahav, G.; Bouza, E.; Lee, C.; Jenkin, G.; Jensen, W.; et al. (N. Engl. J. Med., 2017)

(untitled) - Greig, S. L. (Drugs, 2016)

(untitled) - Migone, T.-S.; Subramanian, G. M.; Zhong, J.; Healey, L. M.; Corey, A.; Devalaraja, M.; Lo, L.; Ullrich, S.; Zimmerman, J.; Chen, A.; Lewis, M.; Meister, G.; et al. (N. Engl. J. Med., 2009)

(untitled) - Dal Peraro, M.; van der Goot, F. G. (Nat. Rev. Microbiol., 2016)

(untitled) - Yu, X.-Q.; Robbie, G. J.; Wu, Y.; Esser, M. T.; Jensen, K.; Schwartz, H. I.; Bellamy, T.; Hernandez-Illas, M.; Jafri, H. S. (Antimicrob. Agents Chemother., 2017)

(untitled) - Karginov, V. A. (Curr. Opin. Pharmacol., 2013)

(untitled) - Ragle, B. E.; Karginov, V. A.; Bubeck Wardenburg, J. (Antimicrob. Agents Chemother., 2010)

(untitled) - Mulvey, G. L.; Marcato, P.; Kitov, P. I.; Sadowska, J.; Bundle, D. R.; Armstrong, G. D. (J. Infect. Dis., 2003)

(untitled) - Kitov, P. I.; Sadowska, J. M.; Mulvey, G.; Armstrong, G. D.; Ling, H.; Pannu, N. S.; Read, R. J.; Bundle, D. R. (Nature, 2000)

(untitled) - Nishikawa, K.; Matsuoka, K.; Kita, E.; Okabe, N.; Mizuguchi, M.; Hino, K.; Miyazawa, S.; Yamasaki, C.; Aoki, J.; Takashima, S.; Yamakawa, Y.; Nishijima, M.; et al. (Proc. Natl. Acad. Sci. U. S. A., 2002)

(untitled) - Zhu, J.; Cai, X.; Harris, T. L.; Gooyit, M.; Wood, M.; Lardy, M.; Janda, K. (Chem. Biol., 2015)

(untitled) - Kany, A. M.; Sikandar, A.; Yahiaoui, S.; Haupenthal, J.; Walter, J.; Empting, M.; Köhnke, J.; Hartmann, R. W. (ACS Chem. Biol., 2018)

(untitled) - Schönauer, E.; Kany, A. M.; Haupenthal, J.; Hüsecken, K.; Hoppe, I. J.; Voos, K.; Yahiaoui, S.; Elsässer, B.; Ducho, C.; Brandstetter, H.; Hartmann, R. W. (J. Am. Chem. Soc., 2017)

Virulence Mechanisms of Bacterial Pathogens - Green, E. R.; Mecsas, J. (Bacterial Secretion Systems: An Overview, 2016)

(untitled) - Duncan, M. C.; Linington, R. G.; Auerbuch, V. (Antimicrob. Agents Chemother., 2012)

(untitled) - Anantharajah, A.; Mingeot-Leclercq, M.-P.; Van Bambeke, F. (Trends Pharmacol. Sci., 2016)

(untitled) - Milla, C. E.; Chmiel, J. F.; Accurso, F. J.; VanDevanter, D. R.; Konstan, M. W.; Yarranton, G.; Geller, D. E. (Pediatr. Pulmonol., 2014)

(untitled) - DiGiandomenico, A.; Keller, A. E.; Gao, C.; Rainey, G. J.; Warrener, P.; Camara, M. M.; Bonnell, J.; Fleming, R.; Bezabeh, B.; Dimasi, N.; Sellman, B. R.; Hilliard, J.; et al. (Sci. Transl. Med., 2014)

(untitled) - Bassler, B. L.; Losick, R. (Cell, 2006)

(untitled) - Tashiro, Y.; Yawata, Y.; Toyofuku, M.; Uchiyama, H.; Nomura, N. (Microbes Environ., 2013)

(untitled) - Galloway, W. R. J. D.; Hodgkinson, J. T.; Bowden, S. D.; Welch, M.; Spring, D. R. (Chem. Rev., 2011)

(untitled) - Geske, G. D.; O'Neill, J. C.; Blackwell, H. E. (Chem. Soc. Rev., 2008)

(untitled) - Köhler, T.; Perron, G. G.; Buckling, A.; van Delden, C. (PLoS Pathog., 2010)

(untitled) - Storz, M. P.; Maurer, C. K.; Zimmer, C.; Wagner, N.; Brengel, C.; de Jong, J. C.; Lucas, S.; Müsken, M.; Häussler, S.; Steinbach, A.; Hartmann, R. W. (J. Am. Chem. Soc., 2012)

(untitled) - Lu, C.; Maurer, C. K.; Kirsch, B.; Steinbach, A.; Hartmann, R. W. (Angew. Chem., Int. Ed., 2014)

(untitled) - Starkey, M.; Lepine, F.; Maura, D.; Bandyopadhaya, A.; Lesic, B.; He, J.; Kitao, T.; Righi, V.; Milot, S.; Tzika, A.; Rahme, L. (PLoS Pathog., 2014)

(untitled) - Ilangovan, A.; Fletcher, M.; Rampioni, G.; Pustelny, C.; Rumbaugh, K.; Heeb, S.; Cámara, M.; Truman, A.; Chhabra, S. R.; Emsley, J.; Williams, P. (PLoS Pathog., 2013)

(untitled) - Kumar, K.; Chopra, S. (J. Antimicrob. Chemother., 2013)

(untitled) - David, M. Z.; Dryden, M.; Gottlieb, T.; Tattevin, P.; Gould, I. M. (Int. J. Antimicrob. Agents, 2017)

Waste from pharmaceutical plants in India and China promotes antibiotic-resistant superbugs - Waxman, H. A.; Corr, B. (Statnews, 2016)

(untitled) - Lübbert, C.; Baars, C.; Dayakar, A.; Lippmann, N.; Rodloff, A. C.; Kinzig, M.; Sörgel, F. (Infection, 2017)